On Finsler s-manifolds (European Journal of Pure and Applied Mathematics, 2017)
‎Finsler $s-$manifolds are a generalization of Riemannian‎ ‎$s-$manifolds‎. ‎An important property of such manifolds is the‎ ‎homogeneity‎. ‎In this paper we study Finsler $s-$manifolds‎. ‎We‎ ‎first construct some example of Finsler $s-$manifolds which are‎ ‎neither Riemannian nor symmetric‎. ‎Then we consider symmetric‎ ‎preserving diffeomorphism of Finsler $s-$manifolds‎. ‎Finally we‎ ‎give some algebraic and existence theorem of these spaces‎.
Keywords: ‎Finsler $s-$manifold‎; ‎Symmetric Finsler space‎; ‎Generalized symmetric space‎; ‎Homogeneous Finsler space